Household transmission of SARS-CoV-2: a prospective observational study in Bosnia and Herzegovina, August–December 2020. (November 2021) - Musa, Sanjin; Kissling, Esther; Valenciano, Marta; Dizdar, Faris; Blažević, Mia; Jogunčić, Anes; Palo, Mirza; Merdrignac, Lore; Pebody, Richard; Jorgensen, Pernille
Highlights: The overall severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) secondary attack rate in this study was 17%. Adults were more likely to be secondary cases than children. Particular care should be taken if primary cases present with cough and rhinorrhoea. Kissing a SARS-CoV-2 case or sharing a meal with a SARS-CoV-2 case increased the risk of infection. Reducing contact in the household immediately is key to prevent onward transmission. ABSTRACT: Background: The secondary attack rate (SAR) of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) was estimated, and the risk factors for infection among members of households with a coronavirus disease 2019 (COVID-19) index case were identified to inform preventive measures. Methods: Between 3 August and 19 December 2020, a household transmission study was implemented based on a standardized World Health Organization protocol. Laboratory-confirmed cases of SARS-CoV-2 infection were recruited through the federal COVID-19 database. Trained contact tracers interviewed index cases and household members to collect information on demographic, clinical and behavioural factors. Contacts were followed up for 28 days to identify secondary infections. SAR was estimated and odds ratios (OR) were calculated for risk factors for transmission. Results: In total, 383 households and 793 contacts were included in this study. The overall SAR was 17% [95% confidence interval (CI) 14–21]. Contacts had higher risk for infection if the primary case had both cough and runny nose (OR 4.31, 95% CI 1.60–11.63), if the contact was aged 18–49 years (OR 4.67, 95% CI 1.83–11.93), if the contact kissed the primary case (OR 3.16, 95% CI 1.19–8.43), or if the contact shared a meal with the primary case (OR 3.10, 95% CI 1.17–8.27). Conclusions: These results add to the global literature by providing evidence from a middle-income setting. Standard preventive measures in households with positive cases remain critical to reduce transmission.